Increased diagnosis and treatment of hepatitis C in prison by universal offer of testing and use of telemedicine. Issue 1 (28th November 2018) - Morey, Sarah; Hamoodi, Abi; Jones, Dee; Young, Tina; Thompson, Craig; Dhuny, Julie; Buchanan, Emma; Miller, Carolyn; Hewett, Margaret; Valappil, Manoj; Hunter, Ewan; McPherson, Stuart
Summary: With recent advances in antiviral therapy, there is an opportunity to eliminate hepatitis C virus (HCV) from the UK population. HCV is common in incarcerated individuals, with previous estimates suggesting 7% of the UK prison population is anti‐HCV antibody positive. Increasing diagnosis and treatment of HCV in prison is a priority in seeking to eliminate transmission in the general population. Thus the study aimed to assess the impact implementation of: (a) A universal offer of blood borne virus testing (UOBBVT) using dry blood spot testing for prisoners at reception to increase diagnosis; (b) Telemedicine clinics (TC) within North East England (NEE) prisons to increase HCV treatment rates. UOBBVT was initially implemented at Her Majesty's Prison (HMP) Durham, commencing March 2016. From March 2016 to February 2017, 2831 of 4280 (66%) new receptions were offered blood borne virus (BBV) testing. Of these, 1495 (53% of offered) accepted BBV testing, of whom 95 (6.4%) were HCV antibody positive, with 47 of those 95 (49.5%) HCV RNA positive, suggesting a prevalence of active infection in the tested population of 3.1% (95% CI 2.4%‐4.2%). Between August 2015 and October 2017, 80 individuals were seen in the TC and 57 (71%) commenced antiviral therapy. Of those with known outcome (n = 29), 100% achieved sustained virological response. In the year prior to implementation, only four patients received HCV treatment. In conclusion, a universal offer of BBV testing to inmates presenting at HMP reception coupled with linkage into specialist care via TC can substantially increase rates of testing, diagnosis and treatment of HCV in this high‐prevalence population.